Social factors and their impact on volunteer work among youth - عثمان سامية (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to identify the impact of social factors (motivation - inhibiting) to participate in volunteer work for youth using the descriptive and analytical approach, and the results have shown the necessity of overcoming the obstacles related to social factors, the most important of which is the general lack of respect for volunteering and volunteers, the absence of an optimal appreciation for the efforts undertaken by the volunteer to rely on Government efforts are only in managing development. As for the driving factors, they are working for the common good, the desire to gain social acceptance, social status among citizens, and a position in charitable societies and social service institutions. While the most important reasons for the reluctance of young people to participate in volunteer work were: the primacy of the private interest over the public interest, lack of time, lack of awareness of the volunteer of the importance of his role, lack of moral incentives.